Methodology for Constructing Form Ontology - U. Ungkawa; D. H. Widyantoro; B. Hendradjaya (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Form ontology was built to complement the knowledge   base   of   XReformer   system,   a   system   to generate web forms design automatically with case-based reasoning  (CBR)  approach.  Case  base  is  used  to  store cases of form design while the ontology is used to define forms and its elements and the relationship between them as well as between the elements itself. The ontology acts as a small-scale knowledge base that can grow to become a big one. The existing ontology development methodologies were too complicated and mature and they were feasible to apply on a large scale ontology. Certainly, it was not efficient to build a small-scale ontology with these highly- discipline  methodologies.  In  this  paper,  we  propose  a simple ontology development methodology but covers all important aspects of the development of ontologies, as an alternative to the existing methodologies.